Association between Smoking and Liver Fibrosis among Patients with Nonalcoholic Fatty Liver Disease - Hongjie Ou; Yaojie Fu; Wei Liao; Caixia Zheng; Xiaolu Wu (Canadian Journal of Gastroenterology and Hepatology)
Objective. We aimed at analyzing the role of smoking in hepatic fibrosis in patients with nonalcoholic fatty liver disease (NAFLD) and at exploring the related risk factors. Methods. This was a cross-sectional study that included a total of 225 patients with NAFLD. Among them, 127 were nonsmokers and 98 were smokers. Liver significant fibrosis was diagnosed when the liver stiffness (LS) value was higher than 7.4 kPa. The diagnostic criterion for NAFLD was a controlled attenuation parameter (CAP) value of >238 dB/m. The CAP and LS values were measured using FibroScan. Results. FibroScan showed that the LS value in the smokers was significantly higher than that in the nonsmokers (10.12 ± 10.38 kPa vs. 7.26 ± 6.42 kPa, P=0.013). The proportions of patients with liver significant fibrosis and advanced liver fibrosis among the smokers were significantly higher than those among the nonsmokers (P=0.046). Univariate analysis showed that age, weight, high AST level, low PLT level, and smoking were the risk factors associated with liver fibrosis in the smokers with NAFLD while multivariate analysis showed that age (OR = 1.029, P=0.021), high AST level (OR = 1.0121, P=0.025), and smoking (OR = 1.294, P=0.015) were the independent risk factors associated with liver fibrosis in the patients with NAFLD. Moreover, high AST level (OR = 1.040, P=0.029), smoking index (OR = 1.220, P=0.019), and diabetes mellitus (OR = 1.054, P=0.032) were the independent risk factors for liver fibrosis among the smokers with NAFLD. Conclusion. This study showed that smoking was closely associated with liver fibrosis among the patients with NAFLD. For patients with NAFLD who smoke, priority screening and timely intervention should be provided if they are at risk of liver fibrosis.